PBL Berbantuan Permainan Catur Termodifikasi: Pengaruh Terhadap Motivasi Belajar Siswa - Widayanti Widayanti; Susadi Susadi; Arini Rosa Sinensis (U-Teach: Journal Education of Young Physics Teacher, 2022)
This study aimed to determine the effect of the application of the PBL model assisted by a modified chess game on students' learning motivation. The research design used is Quasi Experiment Design with Nonequivalent Control Group Design. The research subjects were 8th grade students of SMPN 3 Mesuji Makmur which consisted of 50 students who were divided into experimental class and control class. The results showed that the level of student motivation in the control class was 62.64% in the medium category, while the experimental class scored 82.37% in the high category. Based on hypothesis testing using SPSS 22.0 software through paired samples t-test with a significance level of 5%, the result is 0.00 so that it can be concluded that there is a significant effect on the application of the Problem Based Learning (PBL) model with the help of a modified chess game on the learning motivation of 8th grade students in SMP N 3 Mesuji Makmur